Metal‐based smart nanosystems in cancer immunotherapy - Luo, Ying; He, Xiaojing; Du, Qianying; Xu, Lian; Xu, Jie; Wang, Junrui; Zhang, Wenli; Zhong, Yixin; Guo, Dajing; Liu, Yun; Chen, Xiaoyuan (Exploration (Beijing, China), 2024)
Metals are an emerging topic in cancer immunotherapy that have shown great potential in modulating cancer immunity cycle and promoting antitumor immunity by activating the intrinsic immunostimulatory mechanisms which have been identified in recent years. The main challenge of metal‐assisted immunotherapy lies in the fact that the free metals as ion forms are easily cleared during circulation, and even cause systemic metal toxicity due to the off‐target effects. With the rapid development of nanomedicine, metal‐based smart nanosystems (MSNs) with unique controllable structure become one of the most promising delivery carriers to solve the issue, owing to their various endogenous/external stimuli‐responsiveness to release free metal ions for metalloimmunotherapy. In this review, the state‐of‐the‐art research progress in metal‐related immunotherapy is comprehensively summarized. First, the mainstream mechanisms of MSNs‐assisted immunotherapy will be delineated. The immunological effects of certain metals and categorization of MSNs with different characters and compositions are then provided, followed by the representative exemplar applications of MSNs in cancer treatment, and synergistic combination immunotherapy. Finally, we conclude this review with a summary of the remaining challenges associated with MSNs and provide the authors' perspective on their further advances. Metal‐based smart nanosystems show great potential in modulating each phase of the cancer immunity cycle to boost anticancer immune responses against tumor growth, recurrence, and metastasis mainly by inducing immunogenic cell death, repolarizing protumoral M2 tumor associated macrophages(TAMs) into antitumoral M1 phenotype, and activating the cGAS‐STING signaling pathway.